Exploring Health Literacy in Individuals with Alcohol Addiction: A Mixed Methods Clinical Study - Rolova, Gabriela; Gavurova, Beata; Petruzelka, Benjamin (International journal of environmental research and public health, 2020)
This mixed methods research paper explores health literacy (HL) in individuals with alcohol addiction by using the 47-item version of the European Health Literacy Survey Questionnaire (HLS-EU-Q47) and semi-structured interviews concerning health-related competencies (access, understand, appraise, and apply health information), and determines the limitations of the HLS-EU-Q47 when used under specific conditions of clinical practice. The questionnaire survey and the interviews were conducted with individuals of different health literacy levels who were undergoing inpatient alcohol addiction treatment. The findings indicate that individuals with alcohol addiction might require different types of health information according to their health literacy level in terms of quantity and quality of information to recover from alcohol addiction and improve their overall health. The implications for the clinical practice of addiction treatment as well as recommendations for national and regional policy are also discussed.
Keywords: Alcoholism; Male; HLS-EU-Q47; zdravotní gramotnost; Health Surveys; alcohol addiction; alkoholismus; Adult; dospělí; mužské pohlaví; reprodukovatelnost výsledků; průzkumy a dotazníky; Health Literacy; Reproducibility of Results; inpatient addiction treatment; lidé; ženské pohlaví; health literacy; Humans; zdravotnické přehledy; mixed methods; Female; Surveys and Questionnaires; lidé středního věku; Middle Aged